Cultural Relevance of Physical Activity Intervention Research with Underrepresented Populations. (October 2014) - Conn, Vicki S.; Chan, Keith; Banks, Joanne; Ruppar, Todd M.; Scharff, Jane
This article describes cultural relevance in physical activity intervention research with underrepresented populations. Seventy-one extant studies which tested interventions to increase physical activity among underrepresented adults were included. Verbatim descriptions of efforts to enhance cultural relevance of study designs and interventions were extracted and then content analyzed. We found strategies to enhance cultural relevance of interventions as soliciting input from population members, linking intervention content with values, addressing language and literacy challenges, incorporating population media figures, using culturally relevant forms of physical activity, and addressing specific population linked barriers to activity. Methodological approaches included specialized recruitment and study locations, culturally relevant measures, underrepresented personnel, and cost-awareness study procedures to prevent fiscal barriers to participation. Most reported activities were surface matching. Existing research neither compared the effectiveness of cultural relevance approaches to standardized interventions nor addressed economic, education, geographic, or cultural heterogeneity among groups.